Endoscopic Laser Treatment for Rectosigmoid Villous Adenoma: Factors Affecting the Results - JM Brunetaud; V Maunoury; D Cochelard; B Boniface; A Cortot; JC Paris (Canadian Journal of Gastroenterology)
Endoscopic laser treatment is now commonly used for palliation of advanced digestive cancers in nonsurgical candidates. lt has also been used for treatment of benign rectosigmoid villous adenoma. The present work reports the long term results in 387 patients with benign rectosigmoid villous adenomas revealed by biopsy. Patients included 39% who had contraindications to surgery, 19% who had a tumour recurrence after a nonlaser treatment, 41 % for whom surgical resection appeared to be too drastic for a tumour found benign on biopsy, and 1 % who refused surgery. Two types of wavelength were used: the 1.06 µm infrared light from the Nd:YAG laser and the green light from the argon laser or the Nd:YAG frequency doubled laser. In some patients, both wavelengths were used. Treatment was completed in 343 patients. Total tumour destruction was achieved in 92.8% of patients, a carcinoma was detected in 6.4% on biopsy specimens obtained during laser treatment and benign villous tissue persisted in 0.8%. During the average 30-month follow-up period of the patients with total tumour destruction , 16% had a recurrence. Treatment was well-tolerated with a complication race of 2.3% (one patient with a perforation, one with hemorrhage and seven with stenosis requiring dilation). Circumferential extension of the tumour base was the only factor affecting the duration of treatment, the rate of cancers detected during treatment and the rate of complications. Recurrence rate after initial treatment was higher in patients treated for a recurrence after a previous nonlaser treatment than in patients treated only by laser (P<0.01). It was also higher when the initial histology showed low grade dysplasia as opposed to high grade dysplasia (P<0.01) and when the tumour was located in the lower or middle rectum rather than in the upper rectum or sigmoid (P<0.01). Direct cost of laser treatments was estimated to be 28 to 40% of the surgery charges for lesions of identical size in the authors’ hospital and 31 to 69%, at UCLA Center for the Health Sciences. Because treatment is long and difficult and cancer rate is high, endoscopic laser therapy should be limited in patients with a circumferential villous adenoma to nonsurgical candidates. Risk of complications following surgery has to be balanced against risk of undetected carcinoma and the indication for endoscopic laser treatment should be discussed case by case.